Come By Chance - Hibernia Environmental Assessment Review Panel Meetings. Tape 03. - Memorial University of Newfoundland. Extension Service (Producer) (MUN Extension Service, 1985)
This is the third tape in the Mobil Environmental Assessment Review Panel meetings. This tape continues with questions from the floor copy of MUNES-AT221